Tributação do comércio eletrônico de bens digitais e o princípio da legalidade tributária - Oliveira, Euklenecy Fernandes de (Universidade Federal Rural do Semi-Árido, 2017)
The present research has the objective of analyzing the possibility of the tax hypothesis of the Tax on Operations Relative to the Circulation of Goods (ICMS) on Direct Electronic Commerce, or as commonly called, of digital goods before the Principle of Tax Legality. For this, we initially observe basic concepts related to ICMS and the elementary ones that make up its material criterion. Secondly, the general aspects of Electronic Commerce and its indirect and direct modalities were discussed, the latter being further elaborated by dealing with digital goods and, therefore, constituting a focus of interest in the present work. Soon after, we brought some notes about the current doctrinal and jurisprudential discussion about the incidence of the ICMS on operations related to Electronic Commerce of digital goods. Finally, we sought to study the Principle of Tax Legality, to understand its importance for Tax Law and, therefore, we made a critical conclusion about the legality of ICMS tax on Electronic Commerce of digital goods before the principle of Tax Legality.
Artigo Acadêmico
Keywords: ICMS; Comércio eletrônico direto; Bens digitais; Princípio da legalidade tributária; CIENCIAS SOCIAIS APLICADAS::DIREITO